DEVELOPING PERFORMANCE-BASED BUDGETING MODEL IN PUBLIC SMK IN PURBALINGGA DISTRICT (Universitas Negeri Semarang, 2014)
The planning of education budget plays a strategic role in every school. The budget must be managed, monitored, and evaluated effectively. The aims of this study are (1) to gain a better picture of budgeting model in SMK including its supporting and obstructing factors, (2) to develop a performance-based budgeting model in SMK, (3) to know the effectiveness level of the model, (4) to investigate the response of school managers such as Principals, School Committees, Teachers and Staffs in SMK, (5) to identify the characteristics, strengths, and weaknesses of the model. The budgeting model in SMK is a process, starting from planning, implementation, monitoring, evaluation, and follow up stages. The model is resulted from a Research and Development approach undergoing some stages namely: (1) needs analysis, condition analysis, and theoretical review, (2) conceptual model development, (3) model validation, (4) hypothetical model development, (5) the trial of hypothetical model, (6) the development of empirical model, (7) the trial of empirical model, (8) the development of final model, (9) the dissemination of product. Budgeting process involves an active participation and commitment from school principals, school committees, school vice-principals, head of program, teachers, and staffs in achieving understandable and easy-implemented policy which works effectively.